Level of Anxiety and Community Behavior in Preventing the Covid-19 Pandemic in East Java - Eka Nur So’emah; Emyk Windartik; Ima Rahmawati (Journal of Ners and Midwifery, 2021)
Corona virus-19 (COVID) has been declared a global pandemic. The increase in cases of covid-19 can be prevented by disease prevention behavior in accordance with the protocol that has been established by the government. However, there are still many people who heed the protocol. This condition has an impact on people's anxiety, coupled with the presence of information that continues to be rolled out on social media and mass media about the development of covid-19. Anxiety is increasing with the stigma of the community about covid-19 patients. The purpose of this study was to analyze the level of anxiety and behavior of the community in preventing COVID-19 disease in East Java. The design of the study was descriptive survey. The sample in this study was people in East Java with the sampling techniques by accidental sampling techniques. The data collection used questionnaires using GAD-7. scale and behavior questionnaire according to DIRJEN control and prevention of covid-19 March 2020. The analysis of descriptive statistical test data that was percentile / percentage. The results showed that most people in East Java experience minimal anxiety and positive behavior. Minimal anxiety occured because most respondents are highly educated and already know about Covid-19, this will help solve psychological problems including anxiety. The efforts of health workers are also very much needed to always assist the community in adhering to health protocols by providing sustainable health education.